Early Immune Response Elicited by Different Trypanosoma cruzi Infective Stages - Gutierrez, Brenda Celeste; Lammel, Estela; González-Cappa, Stella Maris; Poncini, Carolina Verónica (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi is a protozoan parasite that affects millions of people in Latin America. Infection occurs by vectorial transmission, by transfusion or transplacental route. Immune events occurring immediately after the parasite entrance are poorly explored. Dendritic cells (DCs) are target for the parasite immune evasion mechanisms. Recently, we have demonstrated that two different populations of DCs display variable activation after the interaction with two infective forms of the parasite, metacyclic or blood trypomastigotes (m or bTp) in vitro. Skin constitutes a complex network with several population of antigen presenting cells. Previously, we have demonstrated Trypanosoma cruzi conditioning the repertoire of cells recruited into the site of infection. In the present work we observed that mTp and bTp displayed differences in cell recruitment to the site of infection and in the activation status of APCs in draining-lymph nodes and spleen during acute infection. Animals inoculated with mTp exhibited 100% of survival with no detectable parasitemia, in contrast with the injected with bTp that displayed high mortality and high parasite load. Animals infected with mTp and challenged with a lethal dose of bTp 15 days after primary infection showed no mortality and incremented DC activation in secondary lymphoid organs compared to controls injected only with bTp or not infected mice. These animals also displayed less number of amastigote-nests in cardiac tissue and more CD8 T cells than mice infected with bTp. All the results suggest that both Tp infective stages induce an unequal immune response since the beginning of the infection.